The frequency of thyroid autoimmunity in behcet’s disease in mid-anatolian region of Turkey (Annals of Medical Research, 2021)
Aim: Behcet’s disease is considered a vasculitis triggered by immunological mechanisms; however its pathogenesis has not been elucidated. The thyroid autoimmune disease frequently coexists with various autoimmune conditions. Studies on the effect of Behcet’s disease on this gland are limited. The present study aimed to examine the presence of thyroid autoimmunity in Behset’s Disease, which has been recently regarded as an autoimmune disease.Material and Methods: The study included 45 patients diagnosed with Behcet’s disease according to the criteria of the International Study Group, and 42 healthy individuals. The levels of FT3, FT4, TSH, thyroglobulin autoantibody (anti-TG) and anti-thyroid peroxidase antibody (anti-TPO), and results of thyroid ultrasonography were examined in all patients and healthy individuals.Results: No significant difference was found in the levels of FT3, TSH and thyroid autoantibodies (anti-TG, anti-TPO) of thyroid function tests between the two groups. FT4 levels were significantly higher in patients with Behcet’s disease compared to the control group (p=0.029).Conclusion: The present study showed that there was no concomitant autoimmune thyroid disease in patients with Behcet’s disease. However, we believe that the vasculitis process might have an impact on parenchyma of the thyroid since FT4 levels were significantly higher in patients, and thus parenchyma of the thyroid should be examined thoroughly in patients with Behcet’s disease.Keywords: Autoimmunity; behcet’s disease; thyroid
Keywords: Autoimmunity; behcet’s disease; thyroid